Secondary Epileptogenesis: Common to See, but Possible to Treat? - Shen, Yujia; Gong, Yiwei; Ruan, Yeping; Chen, Zhong; Xu, Cenglin (Frontiers in Neurology, 2021)
Secondary epileptogenesis is a common phenomenon in epilepsy, characterized by epileptiform discharges from the regions outside the primary focus. It is one of the major reasons for pharmacoresistance and surgical failure. Compared with primary epileptogenesis, the mechanism of secondary epileptogenesis is usually more complex and diverse. In this review, we aim to summarize the characteristics of secondary epileptogenesis from both clinical and laboratory studies in a historical view. Mechanisms of secondary epileptogenesis in molecular, cellular, and circuity levels are further presented. Potential treatments targeting the process are discussed as well. At last, we highlight the importance of circuitry studies, which would further illustrate precise treatments of secondary epileptogenesis in the future.